Câncer da Próstata: sobrevida, fatores associados ao risco de óbito e tendência de mortalidade no Brasil - Sonia Faria Mendes Braga (2016)
Prostate cancer is the second most common kind among men in the whole world. It has been presenting significant mortality incidence rates in Brazil, mainly due to the population ageing. Age is the main risk factor for the development of this cancer, thus the patients may present other ageing related diseases, affecting both survival probability and disease mortality rate. However, these indicators also depend on the quality of the oncologic assistance provided to patients with this neoplasm in the country. Objective: Describe and analyze the global and specific survival, factors associated to death risk and the temporal prostate cancer mortality tendency in Brazil and in the 5 geographic Brazilian regions. Methodology: Two studies were carried out in order to reach this objective. The first was a retrospective study, for which data source was Base Onco, developed by deterministic-probabilistic linkage of the health information systems: outpatient (SIA), hospital (SIH), and mortality (SIM). The global and specific survival probabilities were specified by time passed between the date of the first outpatient treatment, until the death of the patients or end of the study. Fine & gray model of competitive risks regression was used in the evaluation of factors related to specific survival of patients diagnosed with prostate cancer in Brazil. The second study was a temporal series ecologic study, using data from SIM and population data from IBGE, provided by DATASUS. The mortality rates were calculated for Brazil and the geographic regions from 1980 to 2014. APC models were adjusted to identify how age, period and cohort influence the mortality rates. Results: In the first study, the overall survival rate was 0.50 (95% CI: 0.49 to 0.52) and specific for prostate cancer was 0.70 (95% CI: 0.69 to 0.71). Factors associated with risk of death the patients were age at diagnosis (70.5 ± 8.7 years), stage III and IV with HR = 1.66 (95% CI: 1.39 - 1.99) and 3.49 (95% CI: 2.9 - 4.18), respectively; chemotherapy with HR = 2.34 (95% CI: 1,76 - 3.11) and be hospitalized in the SUS with HR = 1.67 (95% CI: 1.55 - 1.79). In the second, mortality rates showed growth trend in Brazil and in 5 geographic regions, especially North and Northeast. The effect of age showed an increased risk with increasing age. The period effect showed lower risk of mortality for the Southeast, South and Midwest and increased risk for North and Northeast. The cohort effect indicates an increased risk among younger cohorts compared to the older, mostly born in the Northeast. Conclusion: These results reinforce the need of effective implantation of the National Oncological Attention Politic, in order to improve access to early diagnosis and treatment of prostate cancer and equally among the entire national territory.